1999
DOI: 10.1088/0953-8984/11/41/306
|View full text |Cite
|
Sign up to set email alerts
|

Constrained variational calculations for many-body spin-polarized atomic deuterium

Abstract: A lowest-order constrained variational (LOCV) method, with modified conditions of healing on the two-body Jastrow wave function, is investigated in calculations for the ground-state energy levels of many-body spin-polarized atomic deuterium. Results are obtained for the , and phases, corresponding to equal occupations of one, two or three nuclear spin states. Estimates for the optimum healing conditions are obtained by comparison of LOCV results with current Monte Carlo benchmarks. The nature of the phases, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 25 publications
(56 reference statements)
1
7
0
Order By: Relevance
“…D↓ atoms obey Fermi statistics and so the zero-pressure state of bulk D↓ depends on the number of occupied nuclear-spin states. In the limit of zero pressure and zero temperature, previous theoretical studies [7][8][9] have shown that ͑D↓ 1 ͒ with only one occupied nuclear-spin state is a gas while bulk D↓ with two ͑D↓ 2 ͒ and three ͑D↓ 3 ͒ equally occupied nuclearspin states remains liquid. Spin-polarized tritium, which obeys Bose statistics, is expected to be liquid [10][11][12] due to its larger mass.…”
Section: Introductionmentioning
confidence: 99%
“…D↓ atoms obey Fermi statistics and so the zero-pressure state of bulk D↓ depends on the number of occupied nuclear-spin states. In the limit of zero pressure and zero temperature, previous theoretical studies [7][8][9] have shown that ͑D↓ 1 ͒ with only one occupied nuclear-spin state is a gas while bulk D↓ with two ͑D↓ 2 ͒ and three ͑D↓ 3 ͒ equally occupied nuclearspin states remains liquid. Spin-polarized tritium, which obeys Bose statistics, is expected to be liquid [10][11][12] due to its larger mass.…”
Section: Introductionmentioning
confidence: 99%
“…Bulk properties of the D↓ system are conditioned by the number of occupied nuclear spin states. [12][13][14] If only one nuclear spin state is occupied ͑D↓ 1 ͒, the system is in a gas state at zero pressure, while in the case of two ͑D↓ 2 ͒ or three ͑D↓ 3 ͒ equally occupied nuclear spin states, the system remains liquid at zero pressure and zero temperature. Extensive investigations of the H↓ and T↓ bulk systems have been carried out recently with the DMC method, 2,6 which provides exact results within error bars for bosonic systems.…”
Section: Introductionmentioning
confidence: 99%
“…(14) are s 1 = 1147(6) KÅ and s 3 = 9.57(2) × 10 6 KÅ 3 . From the functional form (14), and using the corresponding thermodynamic expressions for the pressure (11) and the speed of sound (12), one can easily derive the dependence of these magnitudes on the density. The results for both functions are plotted in Fig.…”
Section: Solid Phasementioning
confidence: 99%